Assessing the Determination of Constructed Normal Value in the 2000 USA Anti Dumping Poultry case in South Africa - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
At the inception of the World Trade Organization (WTO) in 1994, South Africa, as one of the founding members, embarked on a robust trade liberalisation policy. This was mainly achieved through the drastic reduction of tariffs across a number of industries. The agricultural sector was also subjected to this trade liberalisation, which left it open to international competition. As part of the WTO legal framework, the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade 1994 (Anti-Dumping Agreement / ADA) was adopted and all the WTO members were bound by it. The ADA enables a WTO member to impose Anti-Dumping (AD) duties against imports that are being dumped on its domestic market by an exporter of another WTO Member State. In 1999, the South African Poultry Association (SAPA) petitioned the SA AD investigating authority, the Board on Tariffs and Trade (the Board), to impose AD duties on certain USA poultry imports. The Board made use of the constructed NV method, sanctioned by WTO law, to determine NV which resulted in the imposition of final AD duties against USA poultry imports on 9 December 2000. These AD duties were so high that it effectively stopped the importation of USA poultry into the SA market. However, US Government, various interested parties, and scholars have since been very critical of the imposition of the December 2000 AD duties imposed against USA poultry products. It has been argued that the Board egregiously calculated the costs of production of the poultry products, a step vital to the determination of dumping. According to the critics of these AD duties, the Board intentionally made use of the constructed NV method to manipulate cost in order to protect an inefficient and uncompetitive SA poultry industry. So, this study will seeks to test the merits of the argument that the Board?s determination of constructed NV was WTO inconsistent in its December 2000 AD decision against USA poultry products. In doing this, the author will analyse the Board?s decision and WTO Panel reports on the interpretation of Article 2.2.1.1 of the ADA, which deals with the determination of constructed NV.